Optimization technique for grounding grids design / S.Ghoneim ...[et al.] - Ghoneim, S.; Hirsch, H.; Elmorshedy, A.; Amer, R. (UiTM Press, 2008)
A more accurate and practical method to calculate the Earth Surface Potential (ESP) is used. This method is Charge Simulation Method (CSM). A new application is proposed for getting the optimization design of the grounding grids. The basic design quantities of the grounding grids are the ground resistance (Rg), the ground potential rise (GPR), touch and step voltages and the design cost. These mentioned quantities depend on the grid parameters, which are its side lengths and vertical rod length. The dependence of the design quantities of the geometric parameters is given by field computation based on equivalent charges. The effect of number of point charges on the grids, the profile location, and the vertical rod length on ESP is studied. Numerical example is introduced to explain the performance of this method to give valuable information about the grid parameters that satisfy optimization.